Phytomedicines Targeting Cancer Stem Cells: Therapeutic Opportunities and Prospects for Pharmaceutical Development - Piyush Kumar Gupta; Mrunmayee Saraff; Rekha Gahtori; Nidhi Negi; Surya Kant Tripathi; Jatin Kumar; Sanjay Kumar; Saad Hamad Abdullah Aldhayan; Sugapriya Dhanasekaran; Mosleh M. Abomughaid; Kamal Dua; Rohit Gundamaraju; et al. (2021)
The presence of small subpopulations of cells within tumor cells are known as cancer stem cells (CSCs). These cells have been the reason for metastasis, resistance with chemotherapy or radiotherapy, and tumor relapse in several types of cancers. CSCs underwent to epithelial–mesenchymal transition (EMT) and resulted in the development of aggressive tumors. CSCs have potential to modulate numerous signaling pathways including Wnt, Hh, and Notch, therefore increasing the stem-like characteristics of cancer cells. The raised expression of drug efflux pump and suppression of apoptosis has shown increased resistance with anti-cancer drugs. Among many agents which were shown to modulate these, the plant-derived bioactive agents appear to modulate these key regulators and were shown to remove CSCs. This review aims to comprehensively scrutinize the preclinical and clinical studies demonstrating the effects of phytocompounds on CSCs isolated from various tumors. Based on the available convincing literature from preclinical studies, with some clinical data, it is apparent that selective targeting of CSCs with plants, plant preparations, and plant-derived bioactive compounds, termed phytochemicals, may be a promising strategy for the treatment of relapsed cancers.